Improved direct integration auxiliary differential equation FDTD scheme for modeling graphene drude dispersion - Ramadan, Omar (Elsevier Gmbh, 2020)
In this communication, an improved direct-integration auxiliary differential equation (IM-DIADE) scheme is introduced for incorporating graphene's Drude dispersion into the finite difference time domain (FDTD) simulations in the GHz and THz frequency ranges. Stability analysis is performed and it is shown that the time-step stability limit of the presented IM-DI-ADE scheme coincides with the conventional non-dispersive FDTD Courant-Friedrichs-Lewy (CFL) limit and removes the additional stability stringent of the classical DI-ADE counterpart. In addition, the presented scheme does not increase the memory storage overhead. Numerical dispersion analysis is also addressed and it is shown that the presented scheme provides high accuracy. The formulation is validated by numerical tests that investigate the tunneling of electromagnetic wave through a graphene sheet and the existence of the surface plasmon polaritons (SPPs) waves created at the interface between the graphene sheet and a dielectric material.
Keywords: Auxiliary differential equation (ADE); Finite difference time domain (FDTD); Direct-integration; Graphene; Stability analysis; Root-locus; von Neumann; Routh-Hurwitz